2D Polymer Nanonets: Controllable Constructions and Functional Applications. Issue 17 (19th May 2022) - Tang, Ning; Chen, Yu; Li, Yuyao; Yu, Bin
Abstract: 2D polymer nanonets have demonstrated great potential in various application fields due to their integrated advantages of ultrafine diameter, small pore size, high porosity, excellent interconnectivity, and large specific surface area. Here, a comprehensive overview of the controlled constructions of the polymer nanonets derived from electrospinning/netting, direct electronetting, self‐assembly of cellulose nanofibers, and nonsolvent‐induced phase separation is provided. Then, the widely researched multifunctional applications of polymer nanonets in filtration, sensor, tissue engineering, and electricity are also given. Finally, the challenges and possible directions for further developing the polymer nanonets are also intensively highlighted. Abstract : 2D polymer nanonets have presented great potential in various applications, owing to their integrated advantages of ultrafine diameter, small pore size, high porosity, excellent interconnectivity, and large specific surface area. This review comprehensively summarizes recent advances in 2D polymer nanonets with emphasis on the construction strategy and multifunctional applications.